Learning Islamic Religious Education in State Elementary Schools Using Technology-Based Media - Siska, Jumiati; Hadiwinarto, Hadiwinarto (Jurnal Basicedu, 2022)
The purpose of the study is to describe the ability of teachers to use technology-based media, what media teachers use in the teaching and learning process, and what problems teachers face in using technology-based learning media. This research is a field research that uses a qualitative descriptive method, namely by describing the research object as it is. The subjects of this research are the Principal, PAI Teachers and Students. Methods of data collection using observation, interviews and documentation studies. In checking the validity of the data that the writer got in the field, the writer used the triangulation technique, namely; source triangulation, technique triangulation and time triangulation. The research findings show that: first, teachers are able to keep up with the times in using technology-based media in Islamic Religious Education learning, but they do not apply their abilities to the teaching and learning process. Second, in learning tools, Islamic Religious Education teachers have used technology-based learning media although they have not varied, but in reality in the field they only teach conventionally. Third, the problems faced by teachers do not always have a major effect on student learning outcomes. Teachers can carry out their obligations well even though they are not fully supported by learning media.